"Kurica nie ptica, Polsza nie zagranica?” - Kundera, Weronika (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2016)
Polish-Russian relations have been dominated by hatred. The Poles hate everything Russian, Russian products to Russian politics, Russian elites. Historical relations between our countries were dramatic, and in Poland, there is still the historical memory. Moscow, in Polish eyes is "surprising, incalculable and dangerous", and Russia is nothing more "like mafia State of Putin." The Russians are also not free from bias by stating that "Poland sold the West" and makes everything "as long as the only harm Russia". Despitethe close proximity and commonborder, all of these elements effect on no relationship between this two countries. In international relations Poland and Russia are most common in two juxtaposed blocks of political parties, fighting for influence in Ukraine and Belarus. The hope of reconciliation is the future in which people change and systems of values
Keywords: stosunki polsko-rosyjskie; polityka wschodnia; polsko-rosyjskie stereotypy; historia; stosunki międzynarodowe; Polska; Rosja